Politics of Religiousity and the Challenge of Political Development in South–Western Nigeria: Interrogating Issues in Nigeria’s Fourth Republic (Journal of Management and Social Sciences, 2021)
The Nigerian state is composed of various ethnicities. One of the major ethnic groups is Yoruba in the South-western Nigeria. Therefore, the study seeks to unveil Islam and politics in South-western Nigeria since the enthronement of democracy in 1999. The study argues that religious politicization has been detrimental to the unity of the region. Islam was wrongly believed to have no role to play in the society hence the Muslims are marginalized and are not relevant in the political space in Nigeria. The study observes that political apathy on the part of Muslims paved way for Afenifere, a socio-political organization who often pursued a Yoruba agenda but never considered the interests of Muslims as equally important. It is in view of this that the study concludes that, politics and religious consciousness have been exemplary in the political development in the South West since the beginning of the present democratic dispensation. On a final note, the study recommends that Muslims need to get involved and showcase their competence in governance instead of agitation for persistent relevance.KeywordsIslam, Nigeria, politics, Southwest, marginalization